A Syllabus Proposal for Teaching of Software Development Process in Undergraduate Courses in Computer Science - Quaresma, José Augusto Sena; Oliveira, Sandro Ronaldo Bezerra (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
The software development process is the software development approach with tasks, activities, procedures (methods and techniques) and work products. In a world where technology is increasingly needed, having the skills to understand the software development process is essential. In a previous consultation with professionals who work in this area, based on a survey, it was identified that students trained to work in the market do not have all the necessary skills for full professional performance. Therefore, this study seeks to promote a syllabus and a teaching plan for the student-centered teaching and learning process in the software process subject. For the development of this research, a mapping was carried out in the ACM / IEEE computing teaching curriculum in 2013 and in the reference model for the formation of courses by the SBC in 2017 to understand the necessary skills and content. From that moment, the subject was planned with the content divided into three didactic units: Introduction to the software process, Software products and job profiles, and Models and standards for software process and product. Each teaching unit contains prerequisites, guiding questions, study plan, teaching strategy, expected results, learning levels. Learning levels were defined based on Bloom's revised taxonomy. The learning strategies were adopted based on a consultation of the literature and teaching professionals in the area based on a survey. For the evaluation of the syllabus and teaching plan, an expert panel was held with: (i) two researchers fluent in software process, (ii) two professors who are experts in student-centered learning and (iii) one researcher and professor with experience in student-centered learning in the software process subject. The expert panel consisted of a two-part questionnaire, in the first part questions were asked about the identification of the expert's specialty and later questions about the teaching and learning process. A total of five experts evaluated the syllabus and its strategies. The proposed revisions were received and the authors gathered and analyzed each item, justifying its adoption.